Phytochemical screening, antioxidant activity and phenolic content of different plant parts of brucea javanica (L.) / Hidayatul Atiqah Abd Karim, Hamidah Jaafar Sidek and Zurina Mahmud - Abd Karim, Hidayatul Atiqah; Jaafar Sidek, Hamidah; Mahmud, Zurina (Universiti Teknologi MARA, Perlis, 2019)
In this study, phytochemical screening, antioxidant activity as well as phenolic content in the leaves, twigs and barks of Brucea javanica (L.) were determined using standard phytochemical screening method, DPPH radical scavenging assay and Folin-Ciocalteu reagent method, respectively. Methanolic extracts of these different plant parts were prepared by maceration method. Phytochemical screening revealed the presence of flavonoids, terpenoids and tannins in all plant parts. This test also revealed the presence of alkaloids and saponins in all plant parts except they were absent in the twigs and barks parts, respectively. On the other hand, steroids was absent in all plant parts. DPPH method was used to evaluate the antioxidant properties of the plant parts by measuring the absorbance at 517 nm. The antioxidant activity was then compared with standard ascorbic acid. Among all parts, methanolic extract of leaves of Brucea javanica (L.) exhibited the highest antioxidant activity at the concentration of 100 ppm with 86.19 ± 0.20% inhibition which was comparable with standard ascorbic acid with 97.62 ± 0.13% inhibition at the same concentration. The IC50 value of the methanolic extract of leaves was 54.52 ± 0.16 ppm while the other parts were more than 100 ppm. All plant parts showed IC50 value higher than the standard ascorbic acid which recorded IC50 of 9.04 ± 0.09 ppm. The methanolic extract of the leaves also exhibited the highest total phenolic content which was 105.58 ± 0.21 mg GAE/g extract compared to the other parts. This result correlated well with the higher antioxidant activity exhibited by the methanolic extract of the leaves. Thus, the leaves part of methanolic extract of Brucea javanica (L.) exhibited the highest antioxidant activity compared to the other plant parts